Telemedicine Regulation in Indonesia: Legal Frameworks, Challenges, and Future Directions - Mutiah, Fifi; Sibuea, Hotma; Candra, Mardi (Riviera Publishing, 2025)
The rapid advancement of digital technology has positioned telemedicine as a transformative solution to address healthcare disparities, particularly in geographically fragmented regions like Indonesia. Despite its potential, telemedicine adoption in Indonesia faces significant challenges, including regulatory ambiguities, inadequate infrastructure, and concerns over data security and professional accountability. While recent legal frameworks, such as Law No. 17 of 2023 and Government Regulation No. 28 of 2024, aim to address these issues, their implementation remains inconsistent, risking patient safety and trust. This study fills critical gaps in existing literature by integrating the rule of law and health justice frameworks to evaluate Indonesia’s telemedicine regulations—a novel approach absent in prior works. The study addresses two key research questions: (1) How does Indonesia’s current legal framework regulate telemedicine, and what gaps exist in practice? (2) How can telemedicine regulations align with the principles of a legal state (Rechtsstaat) to ensure accountability and equity? Employing a normative juridical methodology, the research combines legislative analysis, conceptual evaluation, and case studies, including the Dr. Damar case (2021), to assess regulatory coherence. Findings reveal significant gaps, including unclear liability standards for misdiagnoses, weak enforcement of data privacy laws, and disparities in rural telemedicine access. The study highlights misalignments with international standards like the GDPR and HIPAA, particularly in AI governance and cross-border data flows. To address these issues, the study recommends: (1) strengthening operational standards by adopting WHO guidelines and mandating AI validation; (2) clarifying liability frameworks to define malpractice accountability; and (3) bridging the digital divide through subsidized internet and device programs.